Simulation and statistical approaches on electrical steel’s magnetic behaviour under unidirectional single sheet tester - Noor Ashikin Mohd Rashid,; Wan Nor Liza Wan Mahadi, (Universiti Kebangsaan Malaysia, 2014)
Evaluation of magnetic properties of electrical steel is vital in improving the quality of electrical machinery since it is used as magnetic cores for transformers, motors and generators. A double yoke single sheet tester (SST) was modeled using two identical C-cores wound with copper wires at limb side in horizontal arrangement. The magnetic properties for electrical steels, grade M4 and M19 were tested under a frequency of 50 Hz with the current ranging from 0.2 to 2.4A. The effects of the sample dimension and anisotropy on magnetic measurements were investigated. Evaluation on specimen dimensions indicate that the non-uniformity of sample magnetization in overhang sample can attribute to the flux leakage between the yoke legs. The stray flux is also increased with the overhang sample. However, the so-called fit-in sample which is fitted nicely between the yoke end poles can minimize the effect of stray flux. One way ANOVA and T-test were used as statistical methods and executed at the 5% significance level. It is statistically proven that the magnetic properties of both magnetic materials are influenced by their anisotropy.